2002
DOI: 10.1038/sj.ijo.0802141
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of tea catechins on diet-induced obesity: stimulation of lipid catabolism in the liver

Abstract: OBJECTIVE: Obesity has increased at an alarming rate in recent years and is now a worldwide health problem. We investigated the effects of long-term feeding with tea catechins, which are naturally occurring polyphenolic compounds widely consumed in Asian countries, on the development of obesity in C57BL=6J mice. DESIGN: We measured body weight, adipose tissue mass and liver fat content in mice fed diets containing either low-fat (5% triglyceride (TG)), high-fat (30% TG), or high-fat supplemented with 0.1 -0.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
379
3
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(415 citation statements)
references
References 26 publications
24
379
3
9
Order By: Relevance
“…In human experiments, consumption of green tea extract, which contains ECG, led to reduced secretion of TNF-α. 15 Furthermore, a study by Siddique et al 26 has demonstrated the protective role of ECG in a transgenic Drosophila model of Parkinson's disease due to its antioxidant and antiapoptotic effects. Tea polyphenols such as ECG have also been shown to inhibit proteasome function, thereby terminating inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human experiments, consumption of green tea extract, which contains ECG, led to reduced secretion of TNF-α. 15 Furthermore, a study by Siddique et al 26 has demonstrated the protective role of ECG in a transgenic Drosophila model of Parkinson's disease due to its antioxidant and antiapoptotic effects. Tea polyphenols such as ECG have also been shown to inhibit proteasome function, thereby terminating inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…14 Gallocatechins have also been asserted to influence molecular targets in signal transduction pathways associated with inflammation, cell death, and survival. 15 In an in vitro study, ECG inhibited the production of pro-inflammatory cytokine, IL-1β, and enhanced the production of anti-inflammatory cytokines, IL-10, in human leukocytes. 16 Kim et al 17 showed that ECG attenuated ROS-induced oxidative stress in human nasal epithelial cells by inhibiting phosphorylation of ERK1/2 and epidermal growth factor receptor.…”
mentioning
confidence: 99%
“…Hence, an alternative approach that can reduce the food intake with minimal side effects emerged as another cautiously accepted choice in obesity control. 5,6 Platycodi Radix (Chinese Jiegeng, Japanese Kikyo, Korean Doraji) is the root of Platycodon grandiflorum A. De (Campanulaceae).…”
Section: Introductionmentioning
confidence: 99%
“…After 11 months of exposure to diets, mice fed a HF diet [30% (w/w)] supplemented with both 0.2 and 0.5% tea catechins had significantly lower weight gains, visceral fat accumulation, and liver fat accumulation in a dosedependent manner compared to the HF control group 99 . Moreover, both green tea catechin treatments suppressed elevation of plasma insulin levels in a dose-dependent manner compared to the HF control 99 .…”
mentioning
confidence: 96%
“…The effects of long-term exposure to green tea catechins on a dietinduced obese model were further explored by Murase et al 99 . After 11 months of exposure to diets, mice fed a HF diet [30% (w/w)] supplemented with both 0.2 and 0.5% tea catechins had significantly lower weight gains, visceral fat accumulation, and liver fat accumulation in a dosedependent manner compared to the HF control group 99 .…”
mentioning
confidence: 99%